Molybdenum and titanium doped single crystal positive electrode material and preparation method and application thereof

By mixing molybdenum and titanium in single crystal positive materials, and using specific preparation methods, the problem of differences in discharge performance and magnification performance of single crystal positive poles, which significantly improves the battery discharge capacity, multiplier performance and cycle life span of the battery Essence

CN119330423AInactive Publication Date: 2025-01-21GEM WUXI ENERGY MATERIAL CO LTD

Patent Information

Application Number
CN202411476216.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

There are differences in discharge performance and rate performance of existing single crystal positive electrode materials, resulting in poor battery performance.

Method used

By mixing molybdenum and titanium into single crystal positive materials, and specific preparation methods, including mixed nickel, cobalt, manganese, molybdenum and titanium elements, the precipitation response and sintering treatment are performed to form the surface rich in titanium -rich elements and the substrate 中 材 中 中 中 中 中 中 中 中.

Benefits of technology

Improving the discharge capacity, multiplier performance and cycle life of the positive pole material, and reducing the electrolyte interface response and the cracks of the crystal material by broadening the LI+transmission channel and inhibiting the release of the lattice oxygen.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330423A_ABST
    Figure CN119330423A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of positive electrode materials, and particularly relates to a molybdenum and titanium doped single crystal positive electrode material and a preparation method and application thereof. The preparation method comprises the following steps: S1, mixing a nickel source, a cobalt source, a manganese source, a molybdenum source, a titanium source and water to obtain a mixed solution, and adding a pH regulator for precipitation reaction to obtain a precursor; wherein the molar weights of nickel, cobalt, manganese, molybdenum and titanium are x, y, z, a and b respectively; x is more than or equal to 0.90% and less than or equal to 0.95%, y is more than or equal to 0.02% and less than or equal to 0.08%, z is more than or equal to 0.01% and less than or equal to 0.08%, a is more than or equal to 0.004% and less than or equal to 0.012%, b is more than or equal to 0.001% and less than or equal to 0.006%, and x + y + z + a + b is 100%; and S2, mixing a lithium source and the precursor, sintering, and crushing to obtain the molybdenum and titanium doped single crystal positive electrode material. The battery containing the positive electrode material has excellent discharge capacity, rate capability and cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of positive electrode materials, and in particular relates to a molybdenum- and titanium-doped single crystal positive electrode material and a preparation method and application thereof. Background Art

[0002] Ternary cathode materials can be divided into polycrystalline materials and single crystal materials. Generally, polycrystalline materials exist in the form of micron-sized agglomerates, and there are a large number of grain boundaries inside the agglomerates. During the battery charging and discharging process, due to the anisotropic lattice changes, polycrystalline materials are prone to grain boundary cracking and secondary particle crushing, which leads to defects such as rapid increase in side reactions, increased impedance, and decreased performance.

[0003] The use of single crystal materials can reduce the number of grain boundaries, reduce the occurrence of side reactions, and increase the compaction density, thereby increasing the energy density. Compared with polycrystalline materials, the cycle performance of single crystal materials is generally much better. However, single crystal positive electrode materials have no grain boundaries inside single crystal materials, and Li + Unlike polycrystalline materials, grain boundaries cannot be used as lithium ion diffusion channels, and Li + The diffusion distance from the interior of a single crystal to the surface is long, so the rate performance of single crystal cathode materials is often worse than that of polycrystalline cathode materials. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defects of poor discharge performance and rate performance of single crystal positive electrode materials in the prior art, thereby providing a molybdenum and titanium doped single crystal positive electrode material and a preparation method and application thereof.

[0005] To this end, the present invention provides the following technical solutions:

[0006] The first aspect of the present invention protects a method for preparing a molybdenum- and titanium-doped single crystal positive electrode material, wherein the preparation method comprises the following steps:

[0007] S1, mixing a nickel source, a cobalt source, a manganese source, a molybdenum source, a titanium source and water to obtain a mixed solution, adding a pH regulator to perform a precipitation reaction to obtain a precursor;

[0008] Among them, the molar amount of nickel element in the nickel source is x, the molar amount of cobalt element in the cobalt source is y, the molar amount of manganese element in the manganese source is z, the molar amount of molybdenum element in the molybdenum source is a, and the molar amount of titanium element in the titanium source is b; in terms of molar percentage, x, y, z, a, and b satisfy 0.90%≤x≤0.95%, 0.02%≤y≤0.08%, 0.01%≤z≤0.08%, 0.004%≤a≤0.012%, 0.001%≤b≤0.006%, and x+y+z+a+b=100%; S2. Mix the lithium source and the precursor, sinter them, and crush them to obtain a molybdenum- and titanium-doped single crystal positive electrode material.

[0009] In the present invention, S1 and S2 are mixed in a conventional manner until they are uniformly mixed.

[0010] According to the present invention, in terms of molar percentage, x, y, z, a, and b satisfy 0.92%≤x≤0.94%, 0.04%≤y≤0.06%, 0.02%≤z≤0.06%, 0.005%≤a≤0.01%, 0.002%≤b≤0.005%, and x+y+z+a+b=100%.

[0011] According to the present invention, the molybdenum source is a soluble molybdenum salt, including (NH4)6Mo7O 24 At least one of 4H2O, K2MoO4, 5H2O, Na2MoO4, (NH4)2MoO4, and (NH4)6Mo7O 24 ·4H2O.

[0012] According to the present invention, the titanium source is a soluble titanium salt, including at least one of TiCl3·6H2O, TiCl3, TiCl4, and Na2TiO3.

[0013] In the present invention, the nickel source, cobalt source, manganese source and water are conventional sources in the field. Typically, but not limiting, the nickel source is a water-soluble nickel salt, including NiSO4·6H2O, Ni(NO3)2·6H2O, NiSO4, NiCl2, Ni(NO3)2, etc.; the cobalt source is a water-soluble cobalt salt, including CoSO4·7H2O, Co(NO3)2·6H2O, Co(NO3)2, CoSO4, CoCl2, etc.; the manganese source is a water-soluble manganese salt, including MnSO4·H2O, Mn(NO3)2·4H2O, Mn(NO3)2, MnSO4, MnCl2, etc.; the water includes deionized water, purified water, etc.

[0014] According to the present invention, the precipitation reaction temperature is 40-60°C and the time is 12-18h.

[0015] In the present invention, the precipitation reaction is carried out under the protection of nitrogen or inert gas. The specific process includes adding water to the pH regulator to prepare a solution, using a peristaltic pump to add the mixed solution and the alkaline solution respectively, and controlling the stirring speed of the reactor to 400-550r / min.

[0016] In the present invention, the pH of the precipitation reaction is conventional in the art, and can make the reaction proceed smoothly. Typically, but not limited to, the pH value is 10-11, and the pH is the pH value of the entire reaction system; the pH adjuster is a conventional pH adjuster in the art, and typically, but not limited to, includes sodium hydroxide solution and ammonia water, and the amounts of the two are adjusted according to actual conditions. Typically, but not limited to, the concentration of the sodium hydroxide solution is 3-5 mol / L, the concentration of the ammonia water is 20-25wt%, and the volume ratio of the sodium hydroxide solution to the ammonia water is 1:10-12.

[0017] In the present invention, after the precipitation reaction is completed, the product obtained by filtration is washed 3-5 times. After being fully washed, it is dried at a temperature of 100-120° C. for 12-18 hours. After drying, a crushing step is performed to finally obtain powder particles.

[0018] According to the present invention, the molar ratio of the lithium element in the lithium source to the sum of the metal elements in the precursor is 1.01-1.05:1.

[0019] In the present invention, the lithium source is a conventional lithium source in the art. Typically, but not limitedly, the lithium source is LiOH·H2O. The metal elements in the precursor include: nickel, cobalt, manganese, molybdenum, and titanium.

[0020] According to the present invention, the sintering is carried out in an oxygen atmosphere, the sintering temperature is 800-900° C., and the sintering time is 12-24 hours.

[0021] The second aspect of the present invention protects a molybdenum and titanium doped single crystal positive electrode material prepared by the above-mentioned preparation method.

[0022] A third aspect of the present invention protects a secondary battery, wherein the secondary battery comprises the aforementioned molybdenum and titanium doped single crystal positive electrode material.

[0023] Preparation of pole pieces: The positive electrode material, acetylene black and PVDF are fully mixed with NMP in a mass ratio of 90:5:5 to form a uniform slurry (solid content is about 35%), the slurry is coated on aluminum foil and dried at 120-125°C for 6-8 hours, and then rolled on a double-roller machine to a thickness of 47-50μm, and then punched into circular pole pieces with a diameter of 12mm using a punching machine. Several pole pieces with no burrs or scratches on the surface and a weight of 17-18mg are selected and dried in a vacuum drying oven at 100-120°C for 2 hours.

[0024] Battery assembly: Place the dried pole piece into an argon-filled glove box with a water content and oxygen content of less than 5ppm, assemble the positive electrode shell, positive pole piece, separator, negative pole piece, negative pole shell and electrolyte into a button cell, and let it stand for 6 hours. The negative pole piece is a metal lithium sheet, the separator is a polyethylene porous membrane, and the electrolyte is a mixture of 1 mol / L LiPF6, ethylene carbonate and diethyl carbonate (the volume ratio of ethylene carbonate and diethyl carbonate is 1:1).

[0025] The technical solution of the present invention has the following advantages:

[0026] 1. The present invention provides a method for preparing a molybdenum- and titanium-doped single crystal positive electrode material, wherein the preparation method comprises the following steps: S1, mixing a nickel source, a cobalt source, a manganese source, a molybdenum source, a titanium source and water to obtain a mixed solution, adding a pH regulator to perform a precipitation reaction, and obtaining a precursor; wherein the molar amount of the nickel element in the nickel source is x, the molar amount of the cobalt element in the cobalt source is y, the molar amount of the manganese element in the manganese source is z, the molar amount of the molybdenum element in the molybdenum source is a, and the titanium The molar amount of titanium in the source is b; in terms of molar percentage, x, y, z, a, and b satisfy 0.90%≤x≤0.95%, 0.02%≤y≤0.08%, 0.01%≤z≤0.08%, 0.004%≤a≤0.012%, 0.001%≤b≤0.006%, and x+y+z+a+b=100%; S2, sintering after mixing the lithium source with the precursor, and crushing to obtain a molybdenum- and titanium-doped single crystal positive electrode material. In the present invention, a specific amount of raw materials is added simultaneously during the precursor preparation process, wherein the molybdenum source and the titanium source have a synergistic effect, and the diffusion rates of the molybdenum element and the titanium element are different, which can form a positive electrode material rich in titanium on the surface while reducing the enrichment of the molybdenum element on the surface, so that the molybdenum element exists in the matrix, and the molybdenum element plays a role in broadening and expanding the positive electrode material Li + Transmission channel function is beneficial to Li + migration, improving the discharge capacity and rate performance of the battery containing the prepared positive electrode material; in addition, molybdenum and titanium doping can inhibit the release of lattice oxygen, reduce the interface reaction with the electrolyte, and reduce the crack impurities of the crystalline material, thereby improving the cycle life of the positive electrode material.

[0027] 2. In the present invention, the specific dosage of each element can further make the dispersion of each element in the prepared positive electrode material more uniform and reasonable, thereby improving the performance of the positive electrode material.

[0028] 3. In the present invention, (NH4)6Mo7O 24 ·4H2O is used together with TiCl3·6H2O, both of which are easily soluble and have high purity, which can further increase the diffusion rate and further improve the performance of the prepared positive electrode material.

[0029] 4. In the present invention, a molybdenum source and a titanium source are first added during the preparation process to obtain a precursor. In this way, the titanium element enriched on the surface will form a Li2TiO4 coating layer on the surface of the positive electrode material during the sintering process of the positive electrode material, which can not only promote the Li + Migration at the interface can also reduce the erosion of the electrolyte on the positive electrode material.

[0030] 5. The present invention provides a molybdenum- and titanium-doped single crystal positive electrode material prepared by the aforementioned preparation method. The positive electrode material has few cracks, the surface of the positive electrode material is rich in titanium, and the matrix is ​​rich in molybdenum. The synergistic effect of the two makes the battery containing the positive electrode material have excellent discharge capacity, rate performance and cycle life.

[0031] 6. The present invention provides a secondary battery, wherein the secondary battery comprises the aforementioned molybdenum and titanium doped single crystal positive electrode material, and the secondary battery has excellent discharge capacity, rate performance and cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 Example 1: Electron microscope image of the molybdenum and titanium doped single crystal positive electrode material obtained. DETAILED DESCRIPTION

[0034] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0035] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0036] Example 1

[0037] This embodiment provides a method for preparing a single crystal positive electrode material doped with molybdenum and titanium, which is specifically as follows:

[0038] S1, according to the molar ratio of nickel element, cobalt element, manganese element, molybdenum element and titanium element of 0.90:0.04:0.05:0.0075:0.0025, NiSO4·6H2O, CoSO4·7H2O, MnSO4·H2O, (NH4)6Mo7O 24 ·4H2O, TiCl3·6H2O and deionized water were mixed to prepare a 2mol / L mixed solution; NaOH was then prepared into a 4mol / L NaOH solution with deionized water, and 20wt% ammonia water and NaOH solution were mixed in a volume ratio of 1:10 to obtain an alkaline solution. The mixed solution was added to the reactor with a peristaltic pump, and the alkaline solution was added with a peristaltic pump at the same time. The pH of the precipitation reaction was controlled to be 10.5, and nitrogen was introduced for protection. The stirring speed of the reactor was controlled to be 500r / min, the reaction temperature was 50°C, and the reaction time was 12h. After the reaction was completed, the filtered product was rinsed with deionized water 4 times, dried at 110°C for 12h, and crushed to obtain the precursor Ni 0.90 Co 0.04 Mn 0.05 Mo 0.0075 Ti 0.0025 (OH)2 powder;

[0039] S2. According to the molar ratio of lithium element to metal element in the precursor powder of 1.02:1, LiOH·H2O and the precursor powder are mixed, sintered at 820°C for 15h in an oxygen atmosphere, and then cooled and crushed to obtain a single crystal positive electrode material doped with molybdenum and titanium, such as Figure 1 As shown, from Figure 1 It can be seen that the positive electrode material prepared in Example 1 presents a single crystal morphology, and no obvious impurities are observed on the surface.

[0040] Example 2

[0041] This embodiment provides a method for preparing a single crystal positive electrode material doped with molybdenum and titanium, which is specifically as follows:

[0042] S1. According to the molar ratio of nickel, cobalt, manganese, molybdenum and titanium being 0.94:0.02:0.03:0.007:0.003, NiSO4·6H2O, CoSO4·7H2O, MnSO4·H2O, Na2MoO4, Na2TiO3 and deionized water are mixed to prepare a 2 mol / L mixed solution; then NaOH is prepared into a 5 mol / L NaOH solution with deionized water, and ammonia water with a concentration of 20 wt% is mixed with the NaOH solution in a volume ratio of 1:12 to obtain an alkaline solution. The mixed solution was added to the reactor by a peristaltic pump, and the alkaline solution was added by a peristaltic pump at the same time. The pH of the precipitation reaction was controlled to be 11, and nitrogen protection was introduced at the same time. The stirring speed of the reactor was controlled to be 450r / min, the reaction temperature was 50°C, and the reaction time was 18h. After the reaction was completed, the filtered product was rinsed with deionized water for 5 times, dried at 120°C for 12h, and crushed to obtain the precursor Ni 0.94 Co 0.02 Mn 0.03 Mo 0.007 Ti 0.003 (OH)2 powder;

[0043] S2. LiOH·H2O and the precursor powder are mixed in a ratio of 1.01:1 between the molar ratio of lithium element and the metal element in the precursor powder, sintered at 850° C. for 12 h in an oxygen atmosphere, and then cooled and crushed to obtain a molybdenum- and titanium-doped single crystal positive electrode material.

[0044] Example 3

[0045] This embodiment provides a method for preparing a single crystal positive electrode material doped with molybdenum and titanium, which is specifically as follows:

[0046] S1 is carried out in the manner of Example 1, except that NiSO4·6H2O, CoSO4·7H2O, MnSO4·H2O, (NH4)6Mo7O are added in a molar ratio of 0.94:0.03:0.015:0.009:0.006 among nickel, cobalt, manganese, molybdenum and titanium. 24 ·4H2O, TiCl3·6H2O and deionized water are mixed;

[0047] S2 is carried out in the manner of Example 1.

[0048] Example 4

[0049] This embodiment provides a method for preparing a single crystal positive electrode material doped with molybdenum and titanium, which is specifically as follows:

[0050] S1 is in the same manner as in Example 1, except that "(NH4)6Mo7O 24·4H2O" to "K2MoO4·5H2O";

[0051] S2 is carried out in the manner of Example 1.

[0052] Example 5

[0053] This embodiment provides a method for preparing a single crystal positive electrode material doped with molybdenum and titanium, which is specifically as follows:

[0054] S1 is in the manner of Example 2;

[0055] S2 is prepared in the manner of Example 2, except that it is sintered at 800° C. for 20 h in an oxygen atmosphere.

[0056] Comparative Example 1

[0057] This comparative example provides a method for preparing a single crystal positive electrode material, which is as follows:

[0058] S1 is in the manner of Example 1, except that NiSO4·6H2O, CoSO4·7H2O, MnSO4·H2O and deionized water are mixed in a molar ratio of nickel element, cobalt element and manganese element of 0.90:0.05:0.05;

[0059] S2 is carried out in the manner of Example 1.

[0060] Comparative Example 2

[0061] This comparative example provides a method for preparing a single crystal positive electrode material doped with molybdenum and titanium, which is as follows:

[0062] S1. According to the molar ratio of nickel, cobalt and manganese of 0.90:0.04:0.05, NiSO4·6H2O, CoSO4·7H2O, MnSO4·H2O and deionized water were mixed to prepare a 2mol / L mixed solution; NaOH was then prepared into a 4mol / L NaOH solution with deionized water, and ammonia water with a concentration of 20wt% and NaOH solution were mixed in a volume ratio of 1:10 to obtain an alkaline solution. The mixed solution was added to the reactor with a peristaltic pump, and the alkaline solution was added with a peristaltic pump at the same time. The pH of the precipitation reaction was controlled to be 10.5, and nitrogen was introduced for protection. The stirring speed of the reactor was controlled to be 500r / min, the reaction temperature was 50℃, and the reaction time was 12h. After the reaction was completed, the filtered product was rinsed with deionized water 4 times, dried at 110℃ for 12h, and crushed to obtain the precursor Ni 0.90 Co 0.04 Mn 0.05 (OH)2 powder;

[0063] S2. According to the molar ratio of lithium, molybdenum, titanium and the metal elements in the precursor powder of 1.02:0.0075:0.0025:1, weigh LiOH·H2O, (NH4)6Mo7O 24 ·4H2O, TiCl3·6H2O and precursor powder are mixed evenly, sintered at 820°C for 15h in an oxygen atmosphere, and then cooled and crushed to obtain a molybdenum- and titanium-doped single crystal positive electrode material.

[0064] Comparative Example 3

[0065] This comparative example provides a method for preparing a titanium-doped single crystal positive electrode material, which is as follows:

[0066] S1 is in the manner of Example 1, except that NiSO4·6H2O, CoSO4·7H2O, MnSO4·H2O, TiCl3·6H2O and deionized water are mixed in a molar ratio of nickel element, cobalt element, manganese element and titanium element of 0.90:0.04:0.05:0.0025;

[0067] S2 is carried out in the manner of Example 1.

[0068] Comparative Example 4

[0069] This comparative example provides a method for preparing a molybdenum-doped single crystal positive electrode material, which is as follows:

[0070] S1 is carried out in the manner of Example 1, except that NiSO4·6H2O, CoSO4·7H2O, MnSO4·H2O, (NH4)6Mo7O are added in a molar ratio of 0.90:0.04:0.05:0.0075 among nickel, cobalt, manganese and molybdenum. 24 4H2O mixed with deionized water;

[0071] S2 is carried out in the manner of Example 1.

[0072] Test Case

[0073] The specific assembly method of the battery is:

[0074] Preparation of pole pieces: The positive electrode material, acetylene black and PVDF were mixed with NMP in a mass ratio of 90:5:5 to form a uniform slurry (solid content of 35%). The slurry was coated on aluminum foil and dried at 120°C for 6 hours. It was then rolled on a roller machine with a thickness of 48 μm. Then, a round pole piece with a diameter of 12 mm was punched out using a punching machine. Several pole pieces with no burrs or scratches on the surface and a weight of 18 mg were selected and dried in a vacuum drying oven at 105°C for 2 hours.

[0075] Battery assembly: Place the dried pole piece into an argon-filled glove box with a water content and oxygen content of less than 5ppm, assemble the positive electrode shell, positive pole piece, separator, negative pole piece, negative electrode shell and electrolyte into a button battery, and let it stand for 6 hours. The negative pole piece is a metal lithium sheet, the separator is a polyethylene porous membrane, and the electrolyte is a mixture of 1 mol / L LiPF6, ethylene carbonate and diethyl carbonate (the volume ratio of ethylene carbonate and diethyl carbonate is 1:1).

[0076] 0.1C discharge capacity test: The battery is charged and discharged at room temperature with a voltage range of 2.8V-4.25V, a nominal specific capacity of 1C=190mAh / g, charged to 4.25V in the first cycle at 0.1C constant current, and then discharged to 2.8V at 0.1C.

[0077] Cycle performance test: charge to 4.25V in the second cycle at 0.2C constant current, then discharge to 2.8V at 0.2C, charge to 4.25V in the third cycle at 0.25C constant current, then discharge to 2.8V at 0.25C, charge to 4.25V in the fourth cycle at 0.5C constant current, then discharge to 2.8V at 0.5C, charge to 4.25V in the 5th-54th cycle at 1.0C constant current, then discharge to 2.8V at 1.0C. The calculation formula is cycle retention rate = discharge capacity in the 54th cycle / discharge capacity in the 5th cycle × 100%.

[0078] Rate performance test: the voltage range is 2.8V-4.25V, and 0.1C rate charge and discharge for 5 cycles, 0.5C rate charge and discharge for 5 cycles, 1C rate charge and discharge for 5 cycles, 3C rate charge and discharge for 5 cycles, and 5C rate charge and discharge for 5 cycles are performed in sequence. The rate performance test results are shown in Table 1. The 0.5C / 0.1C data in the table represents the average discharge capacity of 0.5C rate for 5 cycles / the average discharge capacity of 0.1C rate for 5 cycles; 1.0C / 0.1C represents the average discharge capacity of 1.0C rate for 5 cycles / the average discharge capacity of 0.1C rate for 5 cycles; 3.0C / 0.1C represents the average discharge capacity of 3.0C rate for 5 cycles / the average discharge capacity of 0.1C rate for 5 cycles; 5.0C / 0.1C represents the average discharge capacity of 5.0C rate for 5 cycles / the average discharge capacity of 0.1C rate for 5 cycles.

[0079] The specific test results are shown in Table 1.

[0080] Table 1

[0081]

[0082] The positive electrode material prepared in the present invention is rich in titanium on the surface and rich in molybdenum in the matrix. The two act synergistically, so that the battery containing the positive electrode material has excellent discharge capacity, rate performance and cycle life. As can be seen from Example 1 and Comparative Example 2, firstly, a molybdenum source and a titanium source are added during the preparation process to prepare a precursor. The molybdenum source and the titanium source have a synergistic effect. The diffusion rates of molybdenum and titanium are different, and a positive electrode material rich in titanium on the surface can be formed, reducing the enrichment of molybdenum on the surface, allowing molybdenum to exist in the matrix, and playing the role of molybdenum in broadening and expanding the positive electrode material Li + Transmission channel function is beneficial to Li + migration, improving the discharge capacity and rate performance of the battery containing the prepared positive electrode material; in addition, molybdenum and titanium doping can inhibit the release of lattice oxygen, reduce the interface reaction with the electrolyte, and reduce the crack impurities of the crystalline material, thereby improving the cycle life of the positive electrode material.

[0083] Comparing Example 1 with Example 3, it can be seen that the specific dosage of each element can further make the dispersion of each element in the prepared positive electrode material more uniform and reasonable, thereby improving the performance of the positive electrode material.

[0084] Comparing Example 1 with Example 4, it can be seen that (NH4)6Mo7O 24 ·4H2O is used together with TiCl3·6H2O, both of which are easily soluble and have high purity, which can further increase the diffusion rate, thereby further improving the rate performance of the prepared positive electrode material.

[0085] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A method for preparing a molybdenum and titanium doped single crystal positive electrode material, characterized in that: The preparation method comprises the following steps: S1, mixing a nickel source, a cobalt source, a manganese source, a molybdenum source, a titanium source and water to obtain a mixed solution, adding a pH regulator to perform a precipitation reaction to obtain a precursor; The molar amount of the nickel element in the nickel source is x, the molar amount of the cobalt element in the cobalt source is y, the molar amount of the manganese element in the manganese source is z, the molar amount of the molybdenum element in the molybdenum source is a, and the molar amount of the titanium element in the titanium source is b; in terms of molar percentage, x, y, z, a, and b satisfy 0.90%≤x≤0.95%, 0.02%≤y≤0.08%, 0.01%≤z≤0.08%, 0.004%≤a≤0.012%, 0.001%≤b≤0.006%, and x+y+z+a+b=100%; S2. Mix the lithium source and the precursor, sinter them, cool and crush them to obtain a molybdenum and titanium doped single crystal positive electrode material.

2. The preparation method according to claim 1, characterized in that: In terms of molar percentage, the x, y, z, a and b satisfy 0.92%≤x≤0.94%, 0.04%≤y≤0.06%, 0.02%≤z≤0.06%, 0.005%≤a≤0.01%, 0.002%≤b≤0.005%, and x+y+z+a+b=100%.

3. The preparation method according to claim 1 or 2, characterized in that: The molybdenum source is a soluble molybdenum salt, including (NH4)6Mo7O 24 At least one of 4H2O, K2MoO4, 5H2O, Na2MoO4, and (NH4)2MoO4.

4. The preparation method according to claim 3, characterized in that: The molybdenum source includes (NH4)6Mo7O 24 ·4H2O.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The titanium source is a soluble titanium salt, including at least one of TiCl3·6H2O, TiCl3, TiCl4, and Na2TiO3.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The temperature of the precipitation reaction is 40-60° C. and the time is 12-18 hours.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The molar ratio of the lithium element in the lithium source to the sum of the metal elements in the precursor is 1.01-1.05:

1.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The sintering is carried out in an oxygen atmosphere, the sintering temperature is 800-900° C., and the sintering time is 12-24 hours.

9. A single crystal positive electrode material doped with molybdenum and titanium obtained by the preparation method according to any one of claims 1 to 8.

10. A secondary battery, characterized in that: The secondary battery comprises the molybdenum and titanium doped single crystal positive electrode material according to claim 9.

Citation Information

Patent Citations

  • Lithium ion secondary battery

    CN102315434A

  • Doped and modified high-nickel positive electrode material and preparation method thereof

    CN110504448A

  • Positive electrode active material, preparation method thereof, positive electrode plate and application of positive electrode plate

    CN117088420A

  • Lithium-rich manganese-based material as well as preparation method and application thereof

    CN117776295A

  • Composite doped modified nickel-based positive electrode material and preparation method therefor

    WO2024183609A1

Cited By

  • Lithium-rich manganese-based positive electrode material and preparation method thereof

    CN122177811A

  • A lithium-rich manganese-based positive electrode material and a preparation method thereof

    CN122177811B